My Green School Karya Loynpo Thakur S. Powdyel - Mansurni Abadi (ECOTAS, 2022)
Bhutan is a country that is quite successful in protecting its ecological ecosystem; this is supported by culture and education, which emphasizes students' love of the environment. Even the socio-economic paradigm of the country, which is located between India and China, is the National Happiness Index (GNH) which emphasizing on balance between material and spiritual achievements. There are 33 indicators of happiness which are divided into 9 main aspects of value ranging from psychology, health, time use, education, culture, governance, community creative power, ecological awareness and diversity, and living standards. In the Indonesian context, very few studies discuss how Bhutan balances its spiritual, ecological, and material development. Therefore, this study will examine Loynpo Thakur S Powdyel's book entitled